Behavior of masonry infill panels in RC frames subjected to in plane and out of plane loads - Pereira, Manuel Fernando Paulo (2011)
The building envelope in Europe is usually made of masonry walls, with enclosure and infill functions. Masonry walls have a major economical importance and contribute significantly to the building performance. Even if infill walls have no load-bearing function, they contribute significantly to the seismic behavior of buildings. Therefore, their adequate structural performance is needed, avoiding the occurrence of severe in-plane damage, with very large economical losses, and the out-of-plane expulsion, which additionally represents a large risk for human life. Recent earthquake codes in Europe require the safety assessment of non-structural elements (parapets, veneer masonry walls, infill walls, etc.), when their collapse entails risks for people or for the main structure. The Eurocode standards, entering the mandatory stage now, incorporate new requirements to be fulfilled by buildings or their parts. Such is the case of masonry infilled RC frames whose panels, according to Eurocode 8, are explicitly required to withstand the out-of-plane movement induced by earthquakes. Appropriate measures should be taken to avoid brittle failure and premature disintegration of the infill walls, as well as the partial or total out-of-plane collapse of slender masonry panels. This paper presents the experimental work and results achieved by applying cyclic out-ofplane loads to damaged masonry infilled RC frames. The masonry panels were previously damaged by applying an in-plane cyclic load after which the cyclic out-of- plane loads were applied. The frames and panels tested follow the traditional Portuguese RC structure construction system to which different types of reinforcement have been introduced in the panels.